Low impact leaching agents as remediation media for organotin and metal contaminated sediments. (15th March 2021) - Norén, Anna; Karlfeldt Fedje, Karin; Strömvall, Ann-Margret; Rauch, Sebastien; Andersson-Sköld, Yvonne
Abstract: All over the world, elevated levels of metals and the toxic compound tributyltin (TBT) and its degradation products are found in sediments, especially close to areas associated with shipping and anthropogenic activities. Ports require regular removal of sediments. As a result, large volumes of often contaminated sediments must be managed. The aim of this study was to investigate enhanced leaching as a treatment method for organotin (TBT) and metal (Cu and Zn) contaminated marine sediments. Thus, enabling the possibility to reuse these cleaner masses e.g. in construction. In addition to using acid and alkaline leaching agents that extract the OTs and metals but reduce the management options post treatment, innovative alternatives such as EDDS, hydroxypropyl cellulose, humic acid, iron colloids, ultra-pure Milli-Q water, saponified tall oil ("soap"), and NaCl were tested. Organotin removal ranged from 36 to 75%, where the most efficient leaching agent was Milli-Q water, which was also the leaching agent achieving the highest removal rate for TBT (46%), followed by soap (34%). The TBT reduction accomplished by Milli-Q water and soap leaching enabled a change in Swedish sediment classification from the highest class to the second highest class. The highest reduction of Zn was in HPC leached samples (39% removal) and Cu in EDDS leached samples (33% removal). Although high metal and OT leaching were achieved, none of the investigated leaching agents are sufficiently effective for the removal of both metals and OTs. The results of this study indicate that leaching with ultra-clean water, such as Milli-Q water, may be sufficient to treat TBT contaminated sediments and potentially allow mass reuse. Highlights: Milli-Q was the most efficient leaching agent removing 50% of the TBT from sediment. Hydroxypropyl cellulose (HPC) achieved the highest metal removal from sediment. Saponified tall oil (soap) and HPC treatments lowered the sediment metal risk class. Milli-Q and soap treatments reduced the sediment TBT contamination level class. No leaching agent removed both organotins and metals from the sediments effectively.